Presence of contamination by As Cd, As, Pb, Se, and Hg in coals of the Cundiboyacense area, Colombia - Gómez-Rojas, Olga Patricia; Díaz-Lagos, Mercedes; Blandón-Montes, Astrid; Martínez-Ovalle, Segundo Agustín (Universidad Pedagógica y Tecnológica de Colombia, 2016)
Coals of Cundiboyacense area were studied in order to determine their presence and quantify of content of contaminants such as cadmium (Cd), arsenic (As), lead (Pb), selenium (Se), and mercury (Hg), which are compared with Clarke index for coals of the same rank. Coal samples were taken from active mining fronts and are analyzed by proximate analysis, petrographic and inductively coupled plasma mass spectrometry (ICP-MS). The results show that analyzed samples contained metals such as Pb (15.5 mg•kg-1), Se (16.05 mg•kg-1), Cd (0.55 mg•kg-1) and As (16.05 mg•kg-1) above the world average for coal of the same rank and higher concentrations than the carboniferous area of northern Colombia, the Hg content is low (< 0.08 mg•kg-1). The content of these elements generates environmental concern. According to the Environmental Protection Agency of US (EPA) the maximum allowed for Se, Pb, and Cd is 0.05 mg•kg-1(ppm). It is suggested that conducting specific studies that allow prefetching and / or use of coals.